FAKTOR YANG BERHUBUNGAN DENGAN HAMBATAN DIET DIABETES MELLITUS PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS WONOSARI KABUPATEN BONDOWOSO - Rondhianto, R (FKM - UNEJ, 2013)
Diabetes mellitus type 2 (DM type 2) is chronic disease that needed long term treatment. Diet plays an important role in the management of diabetes, and a suboptimal diet is a commonly identified problem. The objectives of the research are analized factors that related to diet barrier on diabetic patient tipe 2 (individual characteristic, family function and family support). The research is corelational study with 30 outpatient in Wonosari Public Health Center, Bondowoso District. Patients reported on their perception of family functioning, family support for diet, and barriers to diet self-care.The Result of the study indicated, family functioning and family support for diet self-care was related to perceived barriers to diet with negative correlation. (R value = 0,899, double correlation family functioning and family support with perceived barriers to diet). Adjusted R value = 0,794, indicated family functioning and family support contributed 79,4 % to perceived barriers to diet. F value 0,00 <0,05 on double regression explained that family functioning and family support, had influence to perceived barriers to diet. Although individual characterictic have correlation with perceived barriers to diet, but it is not significant (p value > 0,05). The conclusions of the research are family functioning and family support have negative correlation with perceived barriers to diet. As family support for diet increased, perceived barriers to diet decreased. Family approach on diabetic management, especially diet DM education can improve patient self care diabetic management and their family.